(untitled) (Journal of Information Technology and Digital World, 2023)
A zero-day attack refers to a type of cyber-attack that takes advantage of a software vulnerability that is previously unknown to the software vendor or developer. In other words, the attackers exploit a security flaw in a software application before the vendor has had a chance to release a fix (a patch) for it. This term "zero-day" originates from the fact that the developers have had "zero days" to address the vulnerability. In the face of increasingly sophisticated zero-day attacks, the role of future cybersecurity techniques is paramount. Future cybersecurity techniques will emphasize proactive defense measures that go beyond conventional signature-based approaches. These techniques will include advanced anomaly detection, behavior analysis, and predictive modeling to identify zero-day attacks before any damages are caused. The future of cybersecurity techniques will emphasize collaboration across various stakeholders. The significance of a zero-day attack lies in its potential to cause widespread damage and disruption. Zero-day vulnerabilities are unknown to the software vendor and the public, making them an attractive option for cybercriminals and hackers. Because there’s no available fix, attackers can exploit these vulnerabilities without fear of immediate detection or prevention. Since the affected software or hardware isn’t patched, attackers can infiltrate systems and carry out their malicious activities with little resistance. This can result in data breaches, unauthorized access, theft of sensitive information, and more, depending on the attacker’s goals. The proposed study presents a comprehensive view of the threats, detection and the mitigation strategies for the zero-day attacks